Revision of Neotropical genus Echinodexia Brauer & Bergenstamm, 1893 (Diptera: Tachinidae), with new synonymies - Santis, Marcelo Domingos De; Ladeira, Pedro Victor Silva; Nihei, Silvio Shigueo (Zootaxa, 2026)
Three New World genera of Dexiini belonging to a complex characterized by spine-like abdominal setae are revised, namely Echinodexia Brauer & Bergenstamm, 1893, Tropidodexia Townsend, 1915, and Tropidopsiomorpha Townsend, 1927. As a result, two new generic synonymies are proposed: Tropidodexia Townsend, 1915 = Echinodexia Brauer & Bergenstamm, 1893, syn. nov., and Tropidopsiomorpha Townsend, 1927 = Echinodexia Brauer & Bergenstamm, 1893, syn. nov.; along with four new combinations: Echinodexia anthracina (Bigot, 1889), comb. nov., Echinodexia coracina (Wulp, 1891), comb. nov. (with lectotype and paralectotypes designated), Echinodexia lutzi (Townsend, 1915), comb. nov., and Echinodexia tropica (Townsend, 1927), comb. nov. The following specific synonymy is also proposed: Hystrichodexia echinata Wulp, 1891 = Echinodexia anthracina (Bigot, 1889), syn. nov. Finally, a diagnosis for ​Echinodexia and a key to all six known species are given.